E-166 External validation of dawn: benefit seems similar but restrictive selection criteria might omit potential responders. (22nd July 2018) - Blanc, R; Ducroux, C; Khoury, N; Lecler, A; Piotin, M; Fahed, R
Abstract : Purpose: We aimed to conduct an external validation of the selection criteria of the diffusion-weighted-imaging or computerized-tomography-perfusion assessment with clinical mismatch in the triage of wake-up and late-presenting strokes undergoing Neurointervention with Trevo (DAWN) trial 1, 2 in a cohort of unknown onset stroke (UOS) patients treated with thrombectomy. Materials and methods: A study cohort of UOS patients was selected from a prospectively collected thrombectomy database to match the inclusion criteria of DAWN. Patients were stratified according to DAWN Groups A/B/C. Group A criteria identified patients≥80 years old with a NIHSS ≥10 + DWI volume <21 cc; Group B: patients<80 years old with a NIHSS ≥10 + DWI volume <31 cc; and Group C: patients<80 years old with a NIHSS ≥20 + DWI volume ≥31 and<51 cc. We compared proportions of patients with a modified Rankin Scale (mRS)≤2 at 3 months follow-up between DAWN-eligible patients and the study cohort and the DAWN trial thrombectomy group. Results: Out of 102 patients, 60 (59%) were defined as DAWN-eligible. Among these, 26 patients (43%) reached a mRS ≤2 at 3 months follow-up (vs. 52/107 patients [49%] in the DAWN trial thrombectomy group; p=0.52) (figure 1). The proportion of DAWN-ineligible patients for Groups A/B/C with a mRS ≤2 were 2/13 patients (15%), 12/22 patients (55%), and 2/7 patients (29%), respectively. Conclusion: The results of the DAWN trial were externally validated in a UOS cohort where the trial's selection criteria identified a similar proportion of responders to thrombectomy. Additional trials are needed to address benefit in patients with larger infarct volumes who were not eligible for DAWN. References: Jovin TG, Saver JL, Ribo M, et al . Diffusion-weighted imaging or computerized tomography perfusion assessment with clinical mismatch in the triage of wake up and late presenting strokes undergoing neurointervention with Trevo (DAWN) trial methods. Int J Stroke 2017:1747493017710341. Nogueira RG, Jadhav AP, Haussen DC, et al . Thrombectomy 6 to 24 hours after stroke with a mismatch between deficit and infarct. New England Journal of Medicine 2017. Disclosures: R. Blanc: None. C. Ducroux: None. N. Khoury: None. A. Lecler: None. M. Piotin: None. R. Fahed: None.